Peran Promosi dalam Memediasi Wisata-Kuliner terhadap Minat Berkunjung Cirebon - Hediana, Dika; Bakhri, Syaeful; Faozi, Moh. Mabruri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
Cirebon City has very varied tourism potential, but the number of tourist visits to tourist attractions in Cirebon City is less significant than tourist visits from surrounding districts. Cirebon City, which is on the main north coast route, should be an added value for Cirebon City to attract more tourists to visit. The aim of this research is to find out and analyze how tourist attractions, culinary variety and promotions each influence tourists' interest in visiting Cirebon City, as well as how promotions can influence the variables of tourist attraction and culinary variety on visiting interest.The method used in this research is a quantitative approach with a field research type of research. Sampling used proportional sampling of 100.The research results show that tourist attractions and culinary variety have an influence on promotions by 28.1%. Meanwhile, the variables of tourist attraction, culinary variety and promotions influence visiting interest by 36.4%. Promotion cannot mediate the influence of tourist attractions on interest in visiting. Promotion succeeded in mediating the influence of culinary variety on visiting interest.